Recommended Corrective Security Measures to Address the Weaknesses Identified Within the Shapash Nuclear Research Institute - Khadija Moussaid; Oum Keltoum Hakam (International Journal of Nuclear Security, 2018)
The Shapash Nuclear Research Institute (SNRI) data book was issued by the International Atomic Energy Agency (IAEA) in 2013. The hypothetical facility data book describes the hypothetical site, which is divided into two areas: the low-security area, known as the administrative area, and the very high-security area, known as the protected area. The book contains detailed descriptions of each area’s safety and security measures, along with figures of multiple buildings in both areas, and also includes information about the site’s computer networks. This paper aims to identify security weaknesses related to the institute’s location, the Administrative Area (AA), the Protected Area (PA), and the Instrumentation and Control Technology system (ICT) within the SNRI and proposes corrective actions to improve the site’s security measures against malicious acts, based on the IAEA nuclear security series publications, and ultimately proposes a new layout for the whole site and the research reactor building presenting the changes made, using a software called Edraw Max.
Keywords: The Shapash Nuclear Research Institute; Nuclear Security measures; Information Security; Physical Protection system; Hypothetical facility data book